Morphological Features of Cephalic Skeleton of the Adult Black Sea Turbot (Kalkan) Scophthalmus maximus var. maeotica (Pleuronectiformes, Scophthalmidae) - Yelnikov, D.V.; Khanaychenko, A.N. (Вестник зоологии, 2013)
For the first time the full description of neural and visceral cephalic skeleton of adult Black Sea turbot (kalkan), Scophthalmus maximus (Pallas) has been carried out. The detailed outline of the norm of development of cephalic skeleton in adult Black Sea turbot with up-to-date nomenclature of bone elements is offered as a basis to conduct further studies on variability of skeleton elements and abnormalities among the Black Sea turbot morphotypes from natural populations and artificially reared specimens.